Glyphosate resistance in Ambrosia trifida: Part 1. Novel rapid cell death response to glyphosate. Issue 5 (12th April 2017) - Van Horn, Christopher R; Moretti, Marcelo L; Robertson, Renae R; Segobye, Kabelo; Weller, Stephen C; Young, Bryan G; Johnson, William G; Schulz, Burkhard; Green, Amanda C; Jeffery, Taylor; Lespérance, Mackenzie A; Tardif, François J; et al.
Abstract: BACKGROUND: Glyphosate‐resistant (GR) Ambrosia trifida is now present in the midwestern United States and in southwestern Ontario, Canada. Two distinct GR phenotypes are known, including a rapid response (GR RR) phenotype, which exhibits cell death within hours after treatment, and a non‐rapid response (GR NRR) phenotype. The mechanisms of resistance in both GR RR and GR NRR remain unknown. Here, we present a description of the RR phenotype and an investigation of target‐site mechanisms on multiple A. trifida accessions. RESULTS: Glyphosate resistance was confirmed in several accessions, and whole‐plant levels of resistance ranged from 2.3‐ to 7.5‐fold compared with glyphosate‐susceptible (GS) accessions. The two GR phenotypes displayed similar levels of resistance, despite having dramatically different phenotypic responses to glyphosate. Glyphosate resistance was not associated with mutations in EPSPS sequence, increased EPSPS copy number, EPSPS quantity, or EPSPS activity. CONCLUSION: These encompassing results suggest that resistance to glyphosate in these GR RR A. trifida accessions is not conferred by a target‐site resistance mechanism. © 2017 Society of Chemical Industry Abstract : The mechanism of glyphosate resistance in giant ragweed is unknown. This article introduces a unique rapid cell death response to glyphosate and investigates target site resistance mechanisms in giant ragweed.